Investigation of the factors contributing to Indigenous students' retention and attrition rates at the University of Adelaide. Issue 1 (30th August 2021) - Hearn, Shane; Benton, Madeleine; Funnell, Sarah; Marmolejo-Ramos, Fernando
Abstract: Aboriginal and Torres Strait Islander peoples remain significantly under-represented in higher education systems. There are significant disparities in university completion rates for Aboriginal and Torres Strait Islander students compared with their non-Indigenous counterparts. The poor-retention and high-attrition rates among Aboriginal and Torres Strait Islander students come at significant financial and personal cost for the individual, families, community, universities and governments. Existing evidence in relation to attrition has identified complex and multifaceted reasons including ill health, family and community responsibilities, financial difficulties, lack of social support, academic disadvantage and issues surrounding personal well-being. The current study aimed to add to evidence of the academic, financial, social support and well-being factors affecting Aboriginal and Torres Strait Islander student's decision to continue or withdraw from their university studies. Contrary to expectation, students' decision to withdraw was not related to academic and social factors. It was found that students between 22 and 25 years old strongly agreed they were likely to withdraw from studies. There was a significant association between withdrawal and type of enrolment. This study provided important insights into the factors that contribute to a students' decision to withdraw from their university studies, with implications for future educational interventions.